Entrepreneurship education in sports: Issues and challenges - Ansari, P.; Husin, S. (2015)
Much has been said of the importance of entrepreneurship. Entrepreneurs are giving a helping hand to governments in job creation, economical, technological, and social development. The rise of entrepreneurs has already begun. Having agreed on the controversial statement of “Entrepreneurs are made, and Entrepreneurship can be taught”, universities have dipped their toes into the lake of entrepreneurship trying to shape their students as entrepreneurs. However, studies show many have not been successful in this mission. Among academic disciplines, sports is one of those areas that despite enormous opportunities in the industry, along with graduate level knowledge and skills capable of improving daily lives of many, has produced fewer entrepreneurs than it intended; But why? The main reason, according to many experts, is that entrepreneurship education is not practical. The entrepreneurship courses are not productive and the content of such classes doesn’t make a strong bridge between academia and industries; the gap is still there! The question is what is a practical sport entrepreneurship course? Which instructional model is more beneficial for sport students in entrepreneurship classes? This study attempts to answer these questions.